Branding fashion muslim (studi analisis brand wearing klamby) - Alifa Nur Fitri; Silvia Riskha Fabriar; Mustofa Hilmi (Islamic Communication Journal, 2021)
The halal industry in Indonesia is undergoing development. This is supported by 87.17% of Indonesia's population are Muslims. One of the growing industries is the Muslim clothing industry.Â  Modest fashion, a term for fashion trends with a more polite and closed fashion concept. One of the famous Muslim fashions is Wearing Klamby. A local fashion brand from Yogyakarta whose collections have local content. This paper aims to see how Muslim fashion branding is used by Wearing Klamby. During of competition in the Muslim fashion business, branding is an important thing as a form of differentiation with other products, Brand can give life to a product. Branding Wearing Klamby as a product that loves the country is shown with the tagline " The Beauty Indonesia in your daily wear". WearingKlamby is one of the strong fashion products in its Branding. This paper uses a qualitative method with descriptive type with analytic using 7 principles of Fashion Branding according to Bruno Hasson. The data was obtained from social media and news. The results of this paper show that Klamby uses 7 principles of Fashion Branding Bruno Hasson in forming Muslim fashionbranding Wearing Klamby including creating a logo that Stands Out, Building Myths about Brands, Creating evocative Events, using celebrity endorsers, making members as living brand, and do it your way. The existence of the brand can form brand loyalty to consumers Wearing Klamby.